Youth and unemployment: An insight into the entrepreneur sculpture practices of the Nsukka Art School - Chikelue Chris Akabuike (Ianna Journal of Interdisciplinary Studies, 2021)
Background: Scholars have observed thatNigeria as a Third World nation is bedevilled with economic challenges. As a result, many youths have been lunched into poverty and unemployment. Some have lost interest in engaging in apprenticeship which is capable of institutionalizing entrepreneurship. While some in a bid to generate fast income are engaged in illicit means of livelihood. This is worsened asNigeria’s educational institution graduates’ youths who join the labour market annually; with a slim chance of been employed.This situation is attributed to ill-equipped Nigerian students in innovative and entrepreneurial endeavours, owing to the underdeveloped theory in entrepreneurship andarts academic field.